2013
DOI: 10.1103/physreva.87.032307
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement distillation for continuous variables in a thermal environment: Effectiveness of a non-Gaussian operation

Abstract: We study the task of distilling entanglement by a coherent superposition operation tâ+râ † applied to a continuous-variable state under a thermal noise. In particular, we compare the performances of two different strategies, i.e., the non-Gaussian operation tâ + râ † is applied before or after the noisy Gaussian channel. This is closely related to a fundamental problem of whether Gaussian or non-Gaussian entanglement can be more robust under a noisy channel and also provides a useful insight into the practical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Single-photon-level non-Gaussian operations such as photon subtraction [3][4][5][6][7][8][9][10][11][12][13][14][15], photon addition [4,12,16,17] and a coherent superposition of addition and subtraction [18][19][20], here termed photon replacement, are powerful tools which, under certain conditions, can be used to increase entanglement. In the case of photon subtraction, the entanglement-enhancing capability has been experimentally demonstrated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Single-photon-level non-Gaussian operations such as photon subtraction [3][4][5][6][7][8][9][10][11][12][13][14][15], photon addition [4,12,16,17] and a coherent superposition of addition and subtraction [18][19][20], here termed photon replacement, are powerful tools which, under certain conditions, can be used to increase entanglement. In the case of photon subtraction, the entanglement-enhancing capability has been experimentally demonstrated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that teleportation fidelity can be improved by non-Gaussian manipulation on Gaussian entangled states [18][19][20][21][22][23]. In particular, it was shown that a two-mode Gaussian state which does not beat nocloning limit can overcome it by applying non-Gaussian operations [19].…”
Section: B Non-gaussian Manipulationmentioning
confidence: 99%
“…In a variety of studies such as entanglement distillation [17][18][19][20][21][22][23] and robustness of entanglement [24,25], teleportation fidelity has been employed as an operational measure of entanglement to test if an entangled state at hand is a useful resource. For multipartite communications, it is important to know how useful a given multipartite entangled state is in view of performance achieved individually by each pair of users and performance achieved collectively by all users.…”
Section: Introductionmentioning
confidence: 99%
“…When the operations succeed, they amplify an optical field with an amount of noise less than that required as the quantum limit [29][30][31][32][33][34][35]. For two mode systems, they can also distill quantum entanglement of bipartite CV systems even for Gaussian states [36][37][38][39][40] under a noisy environment [38,41] beyond the No-Go theorem of Gaussian regime [42][43][44] and enhance the violation of local realism [45][46][47][48][49]. They can also be useful for quantum communication, e.g., by enhancing the fidelity of the quantum teleportation [39,[50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%